2017
DOI: 10.1038/s41598-017-14881-0
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet and chronic stress aggravate adrenal function abnormality induced by prenatal caffeine exposure in male offspring rats

Abstract: We previously demonstrated thatprenatal caffeine exposure (PCE) suppressed fetal adrenal steroidogenesis and resulted in developmental programming changes in offspring rats. However, whether these changes play a role in adrenal corticosterone synthesis under high-fat diet (HFD) and unpredictable chronic stress (UCS) remains unknown. In present study, rat model was established by PCE (120 mg/kg.d), and male offspring were provided normal diet or HFD after weaning. At postnatal week 21, several rats fed HFD were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 52 publications
(58 reference statements)
2
9
0
Order By: Relevance
“…Similar to our current results, IUGR male rats exposed in utero to maternal tobacco smoke also have increased visceral adiposity in association with increased circulating corticosterone without changing GR-α protein levels 66 . Offspring HFD feeding alone did not change circulating corticosterone levels or 11-β HSD 1 or GR-α mRNA levels in adult rats 79 . In GR knock-out mice, obesity resulting from HFD feeding does not require the GR , whereas obesity resulting from exogenous glucocorticoid administration requires an intact GR , emphasizing the importance of multiple pathways to increased adiposity 80 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our current results, IUGR male rats exposed in utero to maternal tobacco smoke also have increased visceral adiposity in association with increased circulating corticosterone without changing GR-α protein levels 66 . Offspring HFD feeding alone did not change circulating corticosterone levels or 11-β HSD 1 or GR-α mRNA levels in adult rats 79 . In GR knock-out mice, obesity resulting from HFD feeding does not require the GR , whereas obesity resulting from exogenous glucocorticoid administration requires an intact GR , emphasizing the importance of multiple pathways to increased adiposity 80 .…”
Section: Discussionsupporting
confidence: 89%
“…66 Offspring HFD feeding alone did not change circulating corticosterone levels or 11-β HSD 1 or GR-α mRNA levels in adult rats. 79 In GR knock-out mice, obesity resulting from HFD feeding does not require the GR, whereas obesity resulting from exogenous glucocorticoid administration requires an intact GR, emphasizing the importance of multiple pathways to increased adiposity. 80 In our current study, a maternal HFD with or without a post-weaning HFD in non-IUGR male rats (NHR and NHH) increased visceral adiposity and adipocyte size, without changing circulating corticosterone or visceral adipose 11-β HSD 1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, liver TG and TC in the CON group were significantly higher than in the BLK group. Persistent exposure to glucocorticoids induces portal circulation of many fats and promotes ectopic fat storage in the liver and vascular tissues (Dallman et al, 2003;He et al, 2017). Our data showed that serum corticosterone (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Epidemiological investigations have proved that prenatal caffeine exposure (PCE) can cause toxic effects of reproduction and fetal development, such as the increased risk of congenital malformations, premature delivery, spontaneous abortion, IUGR, and susceptibility to chronic diseases [ 21 , 22 ]. Our animal experiments also demonstrated that PCE could not only increase maternal glucocorticoid levels but also cause fetal overexposure to glucocorticoid by inhibiting placental 11β-HSD2, leading to the occurrence of IUGR and susceptibility to multiple chronic diseases in adult offspring [ 16 , 23 26 ]. However, whether caffeine causes IUGR by affecting placental P-gp has not been reported yet.…”
Section: Introductionmentioning
confidence: 83%